Optimal therapy in Gaucher disease - Goker-Alpan, Ozlem (Dove Medical Press, 2010)
Gaucher disease (GD), the inherited deficiency of the lysosomal enzyme glucocerebrosidase, presents with a wide range of symptoms of varying severity, and primarily affects the skeletal, hematologic and nervous systems. To date, the standard of care has included enzyme replacement therapy with imiglucerase. Although imiglucerase is highly effective in reversing the visceral and hematologic manifestations, skeletal disease is slow to respond, pulmonary involvement is relatively resistant, and the CNS involvement is not impacted. Because of the recent manufacturing and processing problems, the research and development of alternative therapeutics has become more pressing. The divergent phenotypes and the heterogeneity involving different organ systems implicates the involvement of several pathological processes that include enzyme deficiency, substrate accumulation, protein misfolding, and macrophage activation, that differ in each patient with GD. Thus, the therapy should be tailored individually in order to target multiple pathways that interplay in GD.